Peningkatan Kecepatan Berhitung Siswa Melalui Penggunaan Metode Jari - Azhar, Imam (MADINAH, 2020)
This research is aimed at overcoming a problem related to students' slow numeracy skills. Therefore, the action research taken to overcome the problem is by using the finger method. The number of research subjects was 20 students. The research approach used is a mixed method approach with Classroom Action Research techniques according to Kemmis & Taggart by using 2 cycles. Research data collection techniques used test and non-test techniques. The data collected was then analyzed by using quantitative and qualitative descriptive data analysis. The results showed that before the treatment, the students needed 6-7 minutes to solve 20 questions, but after the treatment was given in the first cycle, the students took an average of 4-5 minutes to answer 20 questions. Then after treatment II, the students only needed 2-3 minutes to work on 20 questions. From the average score, the students' numeracy test results from cycle I and cycle II were greater than the average pre-test score, which was 66.75 (cycle I) and 76.00 (cycle II) > 54.75 (pre-test). Another finding is, the application of the finger method is able to accommodate a variety of different student learning styles (visual, auditory, and kinesthetic), is able to increase learning motivation and increase students' self-confidence.